Psychological Features of Young Crime Perpetrators - Simonyan , T. (Bulletin of Yerevan University C: Jurisprudence, 2016)
Psychological features of young crime perpetrators are the key to reveal and comprehend the negative factors which instigate a young person to commit a crime. One may admit that these features are the main factors that determine the trends of youth criminality. The following psychological features of young crime perpetrators are analyzed in the article: estrangement, aggressiveness, cruelty, anxiety, etc. Comparative analysis of the psychological features of law-abiding young people and young crime perpetrators shows a significant difference between these two groups.
Keywords: young crime perpetrator, psychological features, estrangement, aggressiveness, cruelty, anxiety, negativism, comparative analysis, negative factors